Escalating the Tourist Revisit Intention on the Heritage Destination with the Memorable Tourism Experiences - Saryatun, Saryatun; Riptiono, Sulis; Nur Azizah, Siti; Muliana Rhamdhani, Intan (Universitas Mercu Buana, 2024)
Objectives: The objective of this research is to investigate the tourists' revisit intention at heritage destinations by testing memorable tourism experiences, destination image, and tourist satisfaction as predictors.Methodology: The heritage destination studied was the Borobudur temple involving a sample of 330 tourists taken using a convenience sampling technique. Data were processed and analyzed using SEM-AMOS.Finding: The results of this research prove that not all components of memorable experience are proven to be significant on destination image, satisfaction, and revisit intention. Destination image can be predicted by the variable’s novelty, local culture, meaningfulness, involvement, and knowledge, while hedonism is not significant. Satisfaction can be predicted by hedonism, novelty, refreshment, meaningfulness, knowledge, and destination image, while local culture and involvement are not significant. Revisit intention is predicted by novelty, local culture, involvement, knowledge, and satisfaction, while hedonism, refreshment, meaningfulness, and destination image are not significant.Conclusion: findings from this research show that local culture is the dominant variable in determining destination image, and novelty is the antecedent that has the greatest influence on satisfaction and revisit intention at heritage destinations.